2013
DOI: 10.1038/sc.2013.46
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with clean intermittent catheterization in spinal cord injury patients: a long-term follow-up study

Abstract: Study design: Retrospective review of medical notes. Objective: To evaluate spinal cord injury (SCI) patients' compliance with bladder emptying method at long-term period after discharge and determine the frequency of urinary tract infections (UTIs). Setting: Inpatient rehabilitation unit of tertiary research hospital. Methods: Bladder management method of 164 new spinal cord injured patients were noted at discharge from rehabilitation center and follow-up. Patients were questioned whether they continued the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
3
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 23 publications
4
81
3
3
Order By: Relevance
“…4,19 However, the occurrence rate of urinary strictures in men with NLUTD using IC for bladder evacuation seems to be higher than previously reported, and the odds of sustaining a stricture are increased in this population. Approximately 25% of men with NLUTD using IC for bladder evacuation can be affected.…”
Section: Discussioncontrasting
confidence: 47%
“…4,19 However, the occurrence rate of urinary strictures in men with NLUTD using IC for bladder evacuation seems to be higher than previously reported, and the odds of sustaining a stricture are increased in this population. Approximately 25% of men with NLUTD using IC for bladder evacuation can be affected.…”
Section: Discussioncontrasting
confidence: 47%
“…In the present study, 41% of the patients used IC for bladder evacuation, which is in accordance with some other reports. 6,17 Other authors have observed lower (that is, 15-33%) 2,14,15,18 or higher (that is, 66-78%) IC rates. 19,20 The discrepancies are the result of differences in the study populations, study designs, national health-care systems and follow-up duration between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,17 However, the reported frequencies of IC following rehabilitation are very heterogeneous. In the present study, 41% of the patients used IC for bladder evacuation, which is in accordance with some other reports.…”
Section: Discussionmentioning
confidence: 99%
“…14 Importantly, the UE function is not the only barrier patients have to the adoption of CIC. Anatomic considerations (gender, BMI), 2,13 uncontrolled incontinence 15 and cognitive impairment following concomitant brain injury 16 may also affect the adoption and continuance of CIC. Thus, increased attention to these areas is necessary.…”
Section: Discussionmentioning
confidence: 99%